Expanding Heritage Horizons through the Cheltenham: A Diaspora Project. Issue 1 (8th October 2020) - Howell, David
This article considers the Cheltenham: Diaspora project, an exploration and promotion of migration heritage narratives in Cheltenham (UK). Cheltenham has a diverse history, but heritage provision in the locality has been consistently concentrated on 18th and 19th century Regency architecture. This has led to a marginalisation of non-elite heritage narratives, with no permanent platform for culturally diverse heritage themes in the region. In addition, informal, online history themed social media groups have, rather than expand heritage narratives, ultimately further narrowed heritage discussions. The Diaspora project looked to challenge the lack of diversity in the authorised heritage discourse, and informal online discourses of Cheltenham's heritage, while enhancing the democratic nature of research projects coming out of the University of Gloucestershire. This paper considers the difficulties encountered in attempting to democratise heritage research, in a cultural climate that is rigid in its perception of what counts as 'heritage' and what is deemed as relevant by more 'vocal' local stakeholder groups. Ultimately the project reveals that while social media provides a useful avenue through which diverse heritage narratives can be pursued and promoted, ingrained attitudes regarding authorised forms of heritage are robust and resistant to the introduction of the unfamiliar.